Infection of Medicago truncatula by the Root-Knot Nematode Meloidogyne javanica Does Not Require Early Nodulation Genes - Costa, Sofia R.; Chin, Sabrina; Mathesius, Ulrike (Frontiers in Plant Science, 2020)
Because of the developmental similarities between root nodules induced by symbiotic rhizobia and root galls formed by parasitic nematodes, we investigated the involvement of nodulation genes in the infection of Medicago truncatula by the root knot nematode (RKN), Meloidogyne javanica. We found that gall formation, including giant cell formation, pericycle and cortical cell division, as well as egg laying, occurred successfully in the non-nodulating mutants nfp1 (nod factor perception1), nin1 (nodule inception1) and nsp2 (nodulation signaling pathway2) and the cytokinin perception mutant cre1 (cytokinin receptor1). Gall and egg formation were significantly reduced in the ethylene insensitive, hypernodulating mutant skl (sickle), and to a lesser extent, in the low nodulation, abscisic acid insensitive mutant latd/nip (lateral root-organ defective/numerous infections and polyphenolics). Despite its supernodulation phenotype, the sunn4 (super numeric nodules4) mutant, which has lost the ability to autoregulate nodule numbers, did not form excessive numbers of galls. Co-inoculation of roots with nematodes and rhizobia significantly reduced nodule numbers compared to rhizobia-only inoculated roots, but only in the hypernodulation mutant skl. Thus, this effect is likely to be influenced by ethylene signaling, but is not likely explained by resource competition between galls and nodules. Co-inoculation with rhizobia also reduced gall numbers compared to nematode-only infected roots, but only in the wild type. Therefore, the protective effect of rhizobia on nematode infection does not clearly depend on nodule number or on Nod factor signaling. Our study demonstrates that early nodulation genes that are essential for successful nodule development are not necessary for nematode-induced gall formation, that gall formation is not under autoregulation of nodulation control, and that ethylene signaling plays a positive role in successful RKN parasitism in M. truncatula.